Transformation Toward Beyond Sustainability: A Community Based Tourism Development Model In North Lombok Regency - Zitri, Ilham; Subandi, Azwar; Pratama, Danur Wenda (Universitas Muhammadiyah Tapanuli Selatan, 2026)
Sustainable tourism development often prioritizes economic growth and environmental protection while giving limited attention to social inclusion and community empowerment. This study explores the transformation of tourism governance in North Lombok Regency, Indonesia, following the 2018 earthquake and the COVID-19 pandemic, through a Beyond Sustainability lens informed by Community-Based Tourism (CBT). Using a descriptive qualitative approach, policy documents and tourism performance data were analyzed through content analysis and social network analysis to examine collaboration among government, community groups, academics, and the private sector. The findings indicate a clear shift from an economy-centered model toward inclusive, community-driven tourism governance. Local government plays a facilitative role by strengthening tourism awareness groups (Pokdarwis), supporting the creative economy, advancing digital promotion, and implementing green tourism policies. Tourism arrivals increased by 113% within two years, local revenue rose by 46%, and tourism villages expanded from five to eight. Network analysis reveals a density of 0.62, with the Senaru Tourism Office and Pokdarwis showing the highest centrality. These results demonstrate that institutionalized multi-actor collaboration and community empowerment provide a transferable policy framework for post-disaster and emerging tourism regions.